Pengaruh Pengetahuan, Akses Kemudahan Digital dan Resiko Terhadap Keputusan Penggunaan QRIS BSI - Rona Afriliani; Usdeldi; M. Yusuf (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze the influence of knowledge, digital accessibility, and perceived risk on the decision to use Bank Syariah Indonesia (BSI) QRIS among Generation Z in Jambi City. The rapid development of digital payment technology has increased the use of Quick Response Code Indonesian Standard (QRIS) as a non-cash transaction method, especially among Generation Z, which is highly adaptive to digital technology. However, several challenges remain, including limited user understanding, ease of application access, and concerns regarding the security risks of digital transactions. This study employed a quantitative approach with an associative research design. The sampling technique used was purposive sampling, involving 100 Generation Z respondents in Jambi City who had used BSI QRIS. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS software. The results showed that knowledge and digital accessibility had a positive and significant effect on the decision to use BSI QRIS, while perceived risk had a negative and significant effect on the decision to use BSI QRIS. Digital accessibility was found to be the most dominant variable influencing QRIS usage decisions. Simultaneously, knowledge, digital accessibility, and perceived risk significantly influenced the decision to use BSI QRIS among Generation Z in Jambi City. This study is expected to serve as an evaluation material for Bank Syariah Indonesia in improving QRIS service quality, strengthening digital transaction security, and enhancing digital literacy among the public